Anti-authoritarian metrics: recursivity as a strategy for post-capitalism - Banks, David Adam (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
This essay proposes that those seeking to build counter-power institutions and communities learn to think in terms of what I call “recursivity.” Recursivity is an anti-authoritarian metric that helps bring about a sensitivity to feedback loops at multiple levels of organization. I begin by describing how technological systems and the socio-economic order co-constitute one-another around efficiency metrics. I then go on to define recursivity as social conditions that contain within them all of the parts and practices for their maturation and expansion, and show how organizations that demonstrate recursivity, like the historical English commons, have been marginalized or destroyed all together. Finally, I show how the ownership of property is inherently antithetical to the closed loops of recursivity. All of this is bookended by a study of urban planning’s recursive beginnings.